2010
DOI: 10.1002/jsfa.4220
|View full text |Cite
|
Sign up to set email alerts
|

Screening for genotype and environment effects on nitrate accumulation in 24 species of young lettuce

Abstract: There is a well-defined sampling window when differences in nitrate accumulation between lettuce genotypes are at a maximum. Delaying sampling may allow morphological changes in head form to mask earlier genotypic differences. Genotype × environment interactions are predominantly of the non-crossover type and have only a small effect on changes in the ranking of accessions between seasons, allowing selections to be made at any time of year. At least part of the genotypic variation in nitrate accumulation is as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 37 publications
0
42
1
1
Order By: Relevance
“…2B), since light is one of the main factors influencing nitrate concentration, which increases in the plant tissue under poor light conditions (winter) (Burns et al 2010). The lack of oxygen did not affect the nitrate content in any cycle (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…2B), since light is one of the main factors influencing nitrate concentration, which increases in the plant tissue under poor light conditions (winter) (Burns et al 2010). The lack of oxygen did not affect the nitrate content in any cycle (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies had shown that Saladin and Iceberg differ significantly in the extent to which they accumulate nitrate (Meacham et al 2003;Burns et al 2011b), and that these differences reflect much of the variability in nitrate concentration observed within a diverse population of young lettuce cultivars in previous screening experiments (Burns et al 2011b). As a result, any progeny from crosses of these two cultivars would be expected to exhibit a wide variability in nitrate accumulation.…”
Section: Plant Materialsmentioning
confidence: 90%
“…The position of the first hole in adjacent gullies alternated between 240 and 480 mm from each end, producing a staggered plant arrangement with a diagonal spacing of about 270 mm between successive gullies, and an average density of 14.2 plants m −2 on each bench. A complete nutrient solution containing nitrate (at 8 mol m −3 ) as the sole N source previously used by Burns et al (2011b), with an adequate concentration of all other nutrients (Hewitt 1966) was continuously pumped from linked storage tanks (with a total capacity of 800 L) to the top end of the eight gullies; this then flowed down the gradient and drained back into the original tanks. This solution was used at half-strength during the first 5 days after transplanting, and at full strength thereafter.…”
Section: Hydroponic Culturementioning
confidence: 99%
“…Although there is strong evidence for the genotypical effects on Cd or nitrate accumulation in vegetable plants (Arao et al, 2003;Burns et al, 2011a;Sugiyama et al, 2011;Wang X et al, 2015;Kristl et al, 2016), less is known about the higher specificity. The present study indicated that no correlation occurred between plant Cd, nitrate, and biomass, suggesting that yield, Cd and nitrate levels may be independent of each other.…”
Section: Discussionmentioning
confidence: 99%
“…(Huang et al, 2015). Nitrate concentration in high-accumulation genotypes was several times greater than that in low-accumulation genotypes, such as lettuce (Lactuca sativa L.) (Escobar-Gutiérrez et al, 2002;Burns et al, 2011a), leaf mustard (Brassica juncea (L.) Czern.) (Sharma et al, 2010), and taro (Colocasia esculenta (L.) Schott) (Kristl et al, 2016).…”
Section: Introductionmentioning
confidence: 99%